Prediction of pharmacokinetic behavior, toxicity and biological activities of alkaloids isolated from Geissospermum laeve (Vell.) Miers (Research, Society and Development, 2020)
This study predicted by in silico methods with the objective of predicting the pharmacokinetic behavior, toxicological and biological activities of alkaloids isolated from Geissospermum laeve. The designs of the molecules and physical-chemical analyzes were made at ChemSketch and Chemicalize.org, the pharmacokinetic behavior and toxicity were made by comparison in the PreADMET and PASS programs online. The results describe that the molecules demonstrate good pharmacokinetic behavior and bioavailability, with emphasis on Geissosquizine, which presents high gastrointestinal permeability, acceptable clearance, being metabolized by CYP 3A4 and greater interaction with target receptors. Pereirina and Vellosiminol presented activities on neuroreceptors, while Flavopererina showed activities of enzymatic modulation, in this way these molecules stood out in relation to the biological activities presented. All substances proved to be toxic and mutagenic, probe studies are needed to aid elucidate their selectivity index. When considering the pharmacokinetic, toxicological and biological aspects we highlight the Pereirin and Vellosiminol show more promising results.